Measuring the permeabilities of binary gas mixtures with a novel time‐lag technique. (10th March 2021) - He, Zhou; Goh, Kheng Lim; Feng, Xianshe; Wang, Kean
Abstract: Measuring permeation properties of gas mixtures is an important but challenging issue. This work reports on a novel time‐lag technique by selectively depositing (ie, desublimation) one of the gas components in a binary mixture at the downstream side using a liquid nitrogen cold trap, thereby allowing for determination of the permeation properties of both permeating components from the pressure response in the permeate chamber. The measurement technique was demonstrated for the permeation of several binary gas mixtures (H2 /CO2, and He /CO2 with various compositions) through a carbon molecular sieve membrane. It was found that the true permeation properties of a binary mixture can be significantly different from the ideal values based on the permeation of pure gas components. This method is time and cost efficient and works well for binary gas mixtures where the difference in the boiling points of the gas components is sufficiently large so that one of the components in the permeate can be selectively desublimated at the permeate side.